Potensi Jenis Pohon Lokal Untuk Pemulihan Lingkungan Lahan Pascatambang Batubara (Studi Kasus di PT Minemex Indonesia) - Anna Nurlia; Hamza Hamza; Bambang Hariyadi (SENTRI: Jurnal Riset Ilmiah, 2026)
Research on the potential of local tree species is crucial for the success of post-coal mining land rehabilitation. By selecting the right species, the revegetation process can be more efficient, sustainable, and provide ecological and economic benefits to the environment and surrounding communities. The implementation of post-coal mining land reclamation must be carried out based on guiding principles, one of which is to maintain environmental sustainability. The application of these principles is crucial as an effort and a form of corporate responsibility, aiming to restore the mined and cleared areas back to their natural functions. Reclamation at PT. Minemex Indonesia is currently in the stage of planting pioneer plants or fast-growing plants (Phase II). Therefore, accurate information is needed regarding the technical aspects of the next reclamation phase (Phase III), which involves planting local trees, to ensure that revegetation goals are met in accordance with the mandates of the Indonesian Ministry of Energy and Mineral Resources Regulation No. 07 of 2014 and the Ministry of Forestry Regulation No. P4/Menhut-II/2011. This study aims to inventory the types of local trees that have the potential for revegetating post-coal mining land at PT. Minemex Indonesia. The identification of local tree species that naturally grow in the forest area around the mine is carried out through vegetation analysis and calculating the importance value index for each species found. Meanwhile, the selection of tree species for revegetation is conducted by scoring based on seven selection criteria: habitus, habitat, regeneration ability, economic value, ecological value, symbiosis, and sprouting ability. Data on soil conditions in the forest area around the mine and the reclamation area are obtained from soil sample analysis. The revegetation plan is developed by considering field data before mining and field data after reclamation. The research results show the discovery of 21 species at the tree level, 24 species at the pole level, 25 species at the sapling level, and 12 tree species at the seedling level that grow naturally in and around the reclamation area of PT. Minemex Indonesia. Based on scoring against the seven selection criteria, there are 12 local tree species that have the potential for use in post-coal mining land revegetation at PT. Minemex Indonesia. These species are Vitex pubescens, Beilschmiedia gemmiflora, Alstonia scholaris, Macaranga gigantea, Bellucia pentamera, Syzygium palembanicum, Cratoxylum arborescens, Aquilaria malaccensis, Durio zibethinus, Syzygium cf. griffithii, Syzygium polyanthum, and Parkia speciosa. The planting of local tree species for post-mining land revegetation is carried out by considering important aspects in the stages of land preparation, nursery, planting, and maintenance.